Nexus between socio-economic development, fiscal decentralization, and environmental quality: Evidence from Indonesia - Ardian Prasetianto; Iwan Kustiwan (Faculty of Islamic Economics and Business of Universitas Islam Negeri Mataram, 2023)
Purpose — The main objective of this study is to analyze the influence of socioeconomic development and fiscal decentralization on environmental quality in Indonesia, as well as to identify causal relationships between them.Method — The data utilized in this study are secondary data collected over the period from 2010 to 2020. Data sources were obtained from the Ministry of Environment and Forestry, the Central Bureau of Statistics, the Ministry of Finance, and the World Bank. This study uses a quantitative approach in dynamic panel data analysis with a generalized method of moments (GMM) estimation analysis. The causal relationship between environmental quality and the research variables is analyzed using the Granger causality test.Result — The study's findings indicate the presence of the reverse of an Environmental Kuznet Curve (EKC) relationship between Gross Regional Domestic Product (GRDP) per capita and environmental quality. Environmental quality is influenced positively and significantly by various factors, including human development, expenditure on environmental functions, poverty, and the manufacturing industry. On the other hand, fiscal transfers and urbanization have a negative and significant effect on environmental quality.Contribution — A more comprehensive analysis of the impact of development achievements in Indonesia on environmental quality indicators is needed at the provincial government level, considering economic development, social development, and governance aspects. This study also classifies research results based on three regional classifications and includes GMM estimation analysis, which has not been widely done.